2020
DOI: 10.1002/pbc.28693
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma for pediatric patients with SARS‐CoV‐2‐associated acute respiratory distress syndrome

Abstract: There are no proven safe and effective therapies for children who develop lifethreatening complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Convalescent plasma (CP) has demonstrated potential benefit in adults with SARS-CoV-2, but has theoretical risks.We present the first report of CP in children with life-threatening coronavirus disease 2019 (COVID-19), providing data on Abbreviations: ADE, antibody-dependent enhancement; CHOP, Children's Hospital of Philadelphia; COVID-19, coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…Following removing duplicates and screening of titles and abstracts, we evaluated 153 articles in full text. Among these, we found 45 relevant articles (4RCTs, 11 controlled NRSIs, 7 non-controlled NRSIs and 23 case reports) [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Extracted details are presented in Table 1 (RCTs, controlled NRSIs, and non-controlled NRSIs) and table 2 (case report(series)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following removing duplicates and screening of titles and abstracts, we evaluated 153 articles in full text. Among these, we found 45 relevant articles (4RCTs, 11 controlled NRSIs, 7 non-controlled NRSIs and 23 case reports) [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Extracted details are presented in Table 1 (RCTs, controlled NRSIs, and non-controlled NRSIs) and table 2 (case report(series)).…”
Section: Resultsmentioning
confidence: 99%
“…case2:7 days after CPT, she showed complete recovery and was discharged. No AEs Diorio C et al [65] USA Case series(n = 4) 14–18 years 200–220 ml 2patients received CP with RBD-specific antibody titer (<1:160), and full-length IgG S titers(>1:1000). 1 patient received CP with RBD-specific antibody titer levels >1:6000 8–15 days Critical illness 1 patient showed transient clinical improvement, decannulating from ECMO, however, died from cardiac.2patients remain in hospital and have had the placement of tracheostomies.…”
Section: Resultsmentioning
confidence: 99%
“… Uneventful complete recovery (47 dys) CP* may be safe and effective treatment option in SARS-CoV-2 infection refractory to remdesivir. Diorio C, et al (Sep 2020) [ 18 ] Case report USA N = 4 patients, 14–18 years old; CD4, CD15, CD17, CD25# None Intubation and ventilation; two required extracorporeal membrane oxygenation RT-PCR*** testing of respiratory tract mucosa Patient CD4 received CP* 2 mL/kg Patients CD15, CD17, CD25 received CP* 4 mL/kg (RBD**-specific antibody titer levels <1:160) Life-threatening COVID-19-associated respiratory disease Donor for patient CD25# had higher SARS-CoV-2 RBD** antibody titers (>1:6000) than donor for other patients; no adverse event CP* may be of greatest benefit early in illness Greene AG, et al (Jun 2020) [ 19 ] Case report USA 11-year-old female None Toxic shock-like syndrome; LV systolic function mildly decreased based on decreased shortening fraction RT-PCR*** positive for SARS-CoV-2 Furosemide, enoxaparin, tocilizumab, CP*, remdesivir, steroids, IVIG Signs of distributive shock, multi-organ injury, systemic inflammation associated with COVID-19 Improved dramatically (24 h) Close follow-up for children presenting with fever lasting 3 dys Balashov D, et al (Nov 2020) [ 24 ] Case report Russia 9-month-old girl Juvenile myelomonocytic leukemia; hematopoietic stem cell transplantation Polysegmental bilateral viral pneumonia with 60 % damage of lung tissue RT-PCR***, throat swab positive for SARS-CoV-2 on day 99 after hematopoietic stem cell transplantation Tocilizumab (10 mg/kg), CP* (10 mL/kg; 3 doses; titers 1:160, 1:160 and 1:80) Secondary immunodeficiency Full resolution of lung lesions; complete elimination SARS-CoV-2 4 mths after first detection CT* well tolerated SARS-CoV-2 CP* in combination with other therapeutic approaches possible curative options Legend...…”
Section: Methodsmentioning
confidence: 99%
“…Although we observed a prompt response to platelet count after the 2nd dose of eculizumab in our patient, he did not exhibit evidence of intravascular hemolysis such as schistocytes on blood smear or hemoglobinuria. A recent study reported the potential efficacy of CP in pediatric patients with SARS-CoV-2 ARDS ( 20 ). Although CP and dexamethasone may have impacted this patient's outcome by reducing the severity of the disease, the improvement in inflammatory markers following complement inhibition correlated with the improved clinical and respiratory status.…”
Section: Discussionmentioning
confidence: 99%